HUBUNGAN ANTARA PENGETAHUAN TENTANG HIPERTENSI DENGAN TINDAKAN MENGONTROL TEKANAN DARAH PADA WARGA DUKUH BANTULAN DESA JEMBUNGAN KECAMATAN BANYUDONO BOYOLALI - Diyono Diyono; Budi Kristanto; Catur Budi Prasetyo (KOSALA : Jurnal Ilmu Kesehatan, 2013)
Background. Hypertension is a leading cause of death in the world. Mostpatients who suffered from hypertension show lack of knowledge about how tocontrol their blood pressure. If the patient doesn’t control their blood pressure, itwill precipitate many complication such as CVA, coronary heart disease (CHD)and cronic kidney disease (CKD).Purpose. The purpose of this study was to determine the relationship betweenknowledge of hypertension and the people’s act to control their blood pressure.Subjects. The subject used in this study was the people of Dukuh Bantulan.The technique sampling was probability sampling and the total number ofresponden were 292 people.Methods. This study used a corelation design with cross sectional approach.Data were collected using a questionaire consist of 18 question duringApril – Mei 2013. Data processing used chi – square statistical test withsignifican level α = 0,03.Result. The result showed x2 count > x2 table (1,524 > 1,074). It can beconcluded that knowledge about hypertension has related to the people’s act tocontrol their blood pessure.Keywords : hypertension, blood pressure